PREVALENCE AND ANTIMICRIBIAL SUSCEPTIBILITY OF ESCHERICHIA COLI O157:H7 ISOLATED FROM HUMAN AND ANIMAL SOURCES IN BASRAH PROVINCE - Bassam Y. Khudaier; Basil A. Abbas; Khulood A. Khleel (Basrah Journal of Veterinary Research)
The present study assessed the prevalence of Escherichia coli O157 in diarrhea patients ,beef, and raw milk. A total of 675 samples were inoculated in trypticase soy broth to enhance the growth of E. coli O157:H7. Out of total samples 73.5% isolated as E. coli then cultured on Sorbitol MacConkey agar ,31.8% non fermenting sorbitol (NSF) E. coli colonies were isolated and confirmed by specific biochemical tests . From NSFEC 13.7% were diagnosed as E.coli O157:H7 by serological test ,the result revealed no significant differences in the level of contamination with E. coli O157:H7 between beef ,stool and milk .The isolated bacteria were tested for antibiotic susceptibility test which showed resistance 100% to cephalothin ,cefoxitin , cefixime, trimethoprim , amoxicillin, azithromycin, and amoxicillin/clavulanic acid and sensitive 100% to ciprofloxacin ,imepenim ,nitrofurantion gentamycin and amikacin . No major differences in antibiotic susceptibility patterns among the isolates were observed.